Alerta nacional: as mulheres enquanto notícia no telejornalismo policial - Aguiar, Larissa Angélica de Santana Madruga Ponce de Leon (2021)
This work aims to reflect on how women are treated in the news of police news coverage, in particular in the program Alerta Nacional, broadcast by Rede TV!. The hypothesis raised is that police television journalism, a hybrid genre, which moves between information and entertainment, giving up ethical parameters, corroborates the discrimination of women, a reprehensible pattern in our society. For this, we used the method of content analysis in which, based on the investigation of the transcripts of ten randomly chosen episodes between January 2020 and March 2021, we were able to collect enough material for the elaboration of categories that helped us in the construction of the results. As a theoretical contribution, we used bibliography on journalism (MARCONDES FILHO, 2000) and, in particular, on television journalism (BUCCI, 1997), given the relationship with our empirical object, as well as using authors who deal with the discussions in around women (BEAUVOIR, 1975; SAFIOTTI, 1987). Finally, we came to the conclusion that inequality between men and women is a reality that gains visibility and, therefore, is reinforced through police journalism when exercised away from its social function of guaranteeing access to quality information by the population, where the importance of our research.